2006
DOI: 10.1029/2005gb002448
|View full text |Cite
|
Sign up to set email alerts
|

A possible sequence of events for the generalized glacial‐interglacial cycle

Abstract: [1] There is not yet widespread agreement as to the underlying cause of the 80-100 ppmv roughly 100-kyr-duration glacial-interglacial cycles in atmospheric pCO 2 . Most of the mechanisms which have been proposed to account for the observed pCO 2 variations appear to in some way violate interpretations of paleo proxy data. The inability of a single mechanism to explain the observed cycles in atmospheric CO 2 (which show amazing similarity over the past 430,000 years) is perplexing, and leads us to consider whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 67 publications
(150 reference statements)
2
68
0
Order By: Relevance
“…Phosphorus speciation in the North Atlantic, particularly the decrease of authigenic and iron bound phases during Heinrich events 4 and 5, points to dysaerobic conditions in the North Atlantic as well (Tamburini et al, 2002). Similarly, mass balance and modeling studies (Boyle, 1988;Broecker, 1982;Francois et al, 1997;Peacock, 2006) have concluded that deep-sea oxygen must have been lower during glacial periods.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus speciation in the North Atlantic, particularly the decrease of authigenic and iron bound phases during Heinrich events 4 and 5, points to dysaerobic conditions in the North Atlantic as well (Tamburini et al, 2002). Similarly, mass balance and modeling studies (Boyle, 1988;Broecker, 1982;Francois et al, 1997;Peacock, 2006) have concluded that deep-sea oxygen must have been lower during glacial periods.…”
Section: Introductionmentioning
confidence: 99%
“…One thing to keep in mind is that the equations solved in LOSCAR are typically stiff and involve different time scales, which requires a solver for stiff problems with adaptive stepsize control. The solver implemented in the C version of LOSCAR is a fourth-order Rosenbrock method with automatic stepsize adjustment (Press et al, 1992).…”
Section: Architecturementioning
confidence: 99%
“…Sarmiento and Toggweiler, 1984;Siegenthaler and Wenk, 1984;Walker and Kasting, 1992;Toggweiler, 1999;Stephens and Keeling, 2000;Köhler et al, 2005;Peacock et al, 2006). However, less studies have coupled a genuine sediment model to the ocean box model (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Preindustrial atmospheric CO 2 concentrations averaged 280 ppm, whereas levels ranging from 180 -200 ppm characterized peak glacial periods [Petit et al, 1999]. While it has been established that these changes in the carbon cycle are closely linked to glacial-interglacial cycles, a set of mechanisms to explain this link has yet to be conclusively established [Archer et al, 2000;Sigman and Boyle, 2000;Peacock et al, 2006]. Consequently, the paleoceanographic community continues to develop and test new hypotheses relating variability in the CO 2 content of the atmosphere to climatic change.…”
Section: Introductionmentioning
confidence: 99%